Gender, politics, news a game of three sides - Ross, Karen 1957- (West Sussex,UK Wiley-Blackwell, 2017)
Gender, Politics, News: A Game of Three Sides explores the role of gender in the broader processes of political communication * The only contemporary book focusing on the relationships between gender, politics, and news media which takes a global perspective * An analysis of political journalism as a practice and the development of the field in terms of gendered workplace cultures * Offers a solid framework for understanding women s political representation, including real world case studies of women s campaigns for the top political job across a range of different geographies and contexts * Coverage of hot-button issues, such as political scandal and the role of new and social media in politics and elections, makes this a highly relevant and current work with resonances for a wide audience.
Introduction -- Women and politics: then and now -- Women in the boyzone -- Women, politics, and campaign coverage: more (or less) bad news -- Girls on top? Winning and losing the political crown -- Behind every great man (or occasionally woman): the political spouse -- Scandalicious: the politics of scandal and the scandal of politics -- Conclusions.
Includes bibliographical references (pages 191-222) and index.
Keywords: Women -- Political activity; Mass media and women